Emotional Intelligence and Job Satisfaction among University Teachers - HAFSA, Ahmed (Journal of Research in Educational Sciences; Vol 6 No 1 (2015): JRES, Volume VI, Issue 1(8), 2015, 2015)
The study aimed to explore the relationship of emotional intelligence on the job satisfaction among university teachers. This research was descriptive in nature. The research objectives included to study the relationship between emotional intelligence and job satisfaction among university teachers and to explore the role of demographic variation such as age, gender, experience, qualification of the university teachers in determining their level of emotional intelligence and their perception about job satisfaction. The population of this study was university teachers of public and private sector universities in Islamabad. A stratified random sample comprised of 50 male and 50 female university teachers were collected from two public and two private universities of Islamabad. Two questionnaires were used for data collection in which one for measuring Job satisfaction while other for measuring emotional intelligence (self-awareness, social skills, self-regulation, motivation, social awareness)of prospective teachers. Data was analyzed with the help of SPSS 16. The major finding of the study concludes that is positive significant correlation between Emotional intelligence and Job satisfaction among public and private sector universities (r=0.78). The study will be beneficial to teachers, researchers, curriculum developer, psychologists and education planners.